An Analysis of Language Features in Local Fashion Brands’ Advertisement on Instagram - Ghina Lugyana; Ernie D. A. Imperiani (Universitas Pendidikan Indonesia (UPI), 2021)
This study attempts to investigate and give a comprehensive account of persuasive techniques and linguistic features in local fashion brands’ advertisements on Instagram, along with the influence of persuasive techniques towards the implementation of linguistic features in the advertisements. To figure it out, this study gathered the data from five captions on recent Instagram posts of Cotton Ink and Look Boutique Store. Using persuasive techniques proposed by Kleppner (1986) and linguistic features in advertising proposed by Grey (2008), the study revealed that the two advertisements had all of three types of persuasive techniques; namely pioneering stage, competitive stage, and retentive stage. In terms of linguistic features, the advertising copywriters used 12 out of 20 types of linguistic features in these two advertisements. Furthermore, the use of persuasive techniques affects the implementation of lexical features in these two brands’ advertisements. Since competitive aims to make the products seem better and unique than the others, the advertisers had to use attractive words or terms to make people believe that the products have a superiority than the other similar products. It also affects the syntactic features, hence the advertisers tend to inform it in long noun phrases with detailed explanations of the products which make them seemed superior. Moreover, the advertisers used present tense to make the customers feel as if the benefits of the superior product they will get will last for a long time. Keywords: Advertisement, Instagram, language feature, linguistic feature, local brand, persuasive language